Third parties’ liability for receipt of misapplied corporate assets: The relevance of knowing receipt? - YIP, Man (Institutional Knowledge at Singapore Management University, 2017)
Thisarticle argues that there are three conceptual difficulties with applying thedoctrine of knowing receipt to cases of receipt of misdirected corporateassets. First, the extension of the doctrine from the trust context to thecorporate context is under explored. It appears to be based on a trust analogybut the analogy is imperfect. Second, many of the cases concern adirector/corporate agent acting without authority. Nevertheless, case law hasyet to fully examine the difficult relationship between want of authority,contractual validity, breach of duty and beneficial receipt. As for the caseswhere the contract is valid but the corporate agent has nonetheless acted inbreach of duty, the contract provides a good justification for the recipient toretain the benefit. Finally, the fundamental differences between the trustframework and the corporate framework justify different forms of protection tobe extended to the beneficiary in each context.